Organisational Baseline Study: Overview report for Tra Hat CSV, Vietnam (VN03) - Truc, Ngo Thi Thanh; Duong, Le Minh; Chi, Truong Thi Ngoc; Phong, Ngo Dang (2015)
This report covers the Organisational Baseline Study (OBS) for the CCAFS Climate-Smart Village Tra Hat in the South Viet Nam. During October 2014 interviews were conducted with local stakeholders at ten organisations who are working or collaborating with farmers and/or the community in Vinh Loi district, Bac Lieu province. The Tra Hat CSV is located near the coastal area, at tail end of a primary canal of Quan Lo Phung Hiep system (QLPH), the Mekong Delta of Vietnam, it usually causes lack of fresh water in from QLPH in dry season. There are two distinct dry season (December to April) and rainy season (May to November) which typhoon happens seldom in rainy season. Protected by dyke and sluice system of QLPH in Bac Lieu province, Tra Hat has not been affected by saline intrusion for last 15 years. The main farming systems in the village comprise two or three rice crops per year, small livestock as pig, chicken and ducks. Besides, mixed fruit garden and cash crop are often blended in residential area. Ground water and water in ponds is popular in household to provide domestic water, raising fish or garden irrigation and livestock, especially in dry season. The objectives of the OBS study are to:  Provide indicators to monitor changes in behaviours and practices of locally relevant organisations that have climate change related activities in Bac Lieu over time  Understand the provision of information/services at the local level that informs farmers’ decision making about their livelihood strategies in response to climate change This OBS report also supplements to the quantitative Household Baseline Survey (HBS) and the qualitative Village Baseline Studies (VBS) in Tra Hat CSV and surrounding villages.